Safety, efficacy and weight effect of two 11β‐HSD1 inhibitors in metformin‐treated patients with type 2 diabetes. Issue 11 (9th June 2014) - Heise, T.; Morrow, L.; Hompesch, M.; Häring, H.‐U.; Kapitza, C.; Abt, M.; Ramsauer, M.; Magnone, M.‐C.; Fuerst‐Recktenwald, S.
<x xml:space="preserve">Abstract</x> Aims We assessed safety and efficacy of two selective 11β‐HSD1 inhibitors (RO5093151/RO‐151 and RO5027383/RO‐838) in this randomized, controlled study in metformin‐treated patients with type 2 diabetes. Methods Patients either received placebo (N = 21), RO‐151 BID 5 mg (N = 24) or 200 mg (N = 20) or RO‐838 QD 50 mg (N = 21) or 200 mg (N = 24) for 28 days. Metabolic assessments comprising of nine‐point plasma glucose profiles, oral glucose tolerance tests and determination of metabolic biomarkers including insulin, C‐peptide, glucagon, HbA1c and lipids were done at baseline and end of treatment. Results Despite the short treatment duration, both RO‐151 and RO‐838 showed trends for improved HbA1c and consistent reductions in body weight (–0.86 to –1.67 kg) exceeding those observed with placebo (–0.28 kg, p = 0.019 for 200 mg RO‐151 vs. placebo). Insulin sensitivity parameters (e.g. HOMA‐IR and Matsuda‐Index) improved non‐significantly with 200 mg RO‐151. Lipid parameters did not consistently improve with either compound, but RO‐838 led to non‐significant increases in triglycerides and VLDL‐cholesterol versus placebo. Both compounds were well tolerated and showed inhibitory effects on 11β‐HSD1 activity based on urinary corticosteroid excretion. As reported for other 11β‐HSD1‐inhibitors increased concentrations of ACTH and adrenal androgen precursors were found with RO‐151, but not with RO‐838. Conclusions Slight metabolic improvements were seen, in particular with RO‐151 high dose, however, the observed changes often did not reach statistical significance and were not clearly dose dependent. Studies of longer duration are needed to further investigate potential benefits and risks of these compounds.